PENGASUHAN DALAM PERKEMBANGAN ANAK DAN REMAJA - Saroya, Tengku Annisa (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2023)
During the time spent youngster advancement, the job of the family can't be isolated from it. A vital job in fostering a kid's character. So the nurturing design given by the family is a significant perspective in shaping a youngster's life. Nurturing is definitely not a simple undertaking. It requires commitment, persistence, understanding, and steady change. There is no such thing as a one-size-fits-all approach to parenting because every child is unique and has unique requirements and characteristics. In setting up this article, an exploration strategy was utilized, to be specific writing survey or writing audit. Assess and examine each source to shape a complete system and understanding. Authoritarian, authoritative, and permissive parenting patterns were identified as the most common parenting styles, according to the findings. In nurturing, a few guardians will deal with issues of philanthropy, hostility and dread. So in nurturing you need to focus on how nurturing designs shape the kid's character, what the outcomes of misuse and disregard the kid appearances, and what occurs in the event that the guardians commit errors in focusing on the kid.